Factors Influencing CEO Compensation in Companies Listed on The LQ-45 Index of The Indonesia Stock Exchange 2016-2020 - Wijaya, Liliana; Ismanto, Christin; Marciano, Deddy (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The purpose of this study is to find out the influence of tobin's-q, return on asset, women as CEO, board independence, institutional ownership, concentrated ownership, and firm size towards CEO compensation in companies listed on LQ-45 Index of the Indonesia Stock Exchange for the period of 2016-2020. This study uses a quantitative perspective with a linear regression model and data panel. The number of 205 data was observed continuously for five years according to the sample characteristics. Test model specifications with the Chow test and Hausman test shows that random effect models using white correction provide the most suitable results. The results showed that tobin's-q, women as CEO and firm sizes have a significant positive effect on CEO compensation. Meanwhile, institutional ownership has a significant negative effect on CEO compensation. The test results show return on assets and concentration ownership have no effect on CEO compensation. The contribution of this research can provide input for investors and management to understand the conditions of female executives' compensation and the factors that have fundamentally proven to affect the compensation of CEOs. Furthermore, these results have a strong reliability to be considered in designing executive compensation packages and good governance systems. Keywords: tobin's-q, women as ceo, institutional ownership, firm size, ceo compensation